Towards a Valorization of Corn Bioethanol Side Streams: Chemical Characterization of Post Fermentation Corn Oil and Thin Stillage - Gabriella Di Lena; Petra Ondrejíčková; Josè Sanchez del Pulgar; Veronika Cyprichová; Tomáš Ježovič; Massimo Lucarini; Ginevra Lombardi Boccia; Stefano Ferrari Nicoli; Paolo Gabrielli; Altero Aguzzi; Irene Casini; Roberto Caproni (Molecules, 2020)
First-generation biofuel biorefineries may be a starting point for the development of new value chains, as their by-products and side streams retain nutrients and valuable molecules that may be recovered and valorized for high-value applications. This study provides a chemical characterization of post-fermentation corn oil and thin stillage, side streams of dry-grind corn bioethanol production, in view of their valorization. An overall long-term study was conducted on the two co-products collected over 1 year from a bioethanol plant. Water content, acid value, sedimentation, mineral composition, and fatty acid profiles were analyzed on post-fermentation corn oil. Results highlighted that its acid value was high (19.72–24.29 mg KOH/g), indicating high levels of free fatty acids, but stable over the year due to standardized operating conditions. The fatty acid profile was that typical of corn oil, with a prevalence of linoleic (54–59% of total fatty acids) over oleic (23–27%) and palmitic (12–17%) acids. Macronutrients, fatty acid, and mineral profiles were investigated in thin stillage. Results revealed the acidic pH (4.05–4.68) and high dilution (90–93% water) of this side stream. The dry mass was composed of fats (19–30%), proteins (8.8–12.8%), ash (8.7–9.5%), and fiber (7.3–9.8%). The concomitant presence of a variegate complex of molecules of nutritional interest in corn bioethanol co-products, with several potential high-value market applications, make the perspective of their recovery a promising strategy to create new cross-sector interconnections according to circular economy principles.